Job Satisfaction with The Performance of Employees of PT. Pos Indonesia (Persero) Dumai Branch - Hartutik, Dwi; Lastri, Novelma; Suherman, S.; Musdiana, Andi Desy (Golden Ratio of Data in Summary, 2024)
Employee satisfaction at work is certainly inseparable from the company's role in managing its employees. The satisfaction that arises will certainly have a positive impact on increasing work productivity. This research was conducted with the aim of determining the effect of job satisfaction on the performance of employees of PT. Pos Indonesia (Persero) Dumai Branch. The symptoms encountered such as the suboptimal availability of work support facilities, frequent employee turnover and the finding of several results of employee work assessments that declined became the starting point for this study. The location of the research is PT Pos Indonesia Dumai Branch. The study used a survey involving a sample of 35 people with a census sampling technique. The results of the study were obtained that there was an effect of job satisfaction on employee performance to increase the company's revenue results with details of job satisfaction results of 69.3% and employee performance of 73.8%. Further research in the future is very necessary for scientific development, especially in looking at the relationship between job satisfaction and employee performance.